THEORETICAL FOUNDATIONS OF CALCULATION OF THE COST OF MEDICAL SERVICES - YEREMІAN, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Calculating the cost of medical services is an important aspect of healthcare management that affects decision-making, pricing and the overall efficiency of medical institutions. The article investigates and summarizes the theoretical foundations of cost medical services with regard to the specifics of the healthcare industry.The study emphasizes the complexity of determining costs in a market economy, as various fundamental concepts, such as cost accounting objects, costing units, and cost allocation methods, are important for accurate calculations. The choice of the costing method is particularly important, as it affects the formation of economically justified costs and the ability to analyze and optimize costs. The article emphasizes the need for an individual approach to cost accounting in healthcare institutions, suggesting that the object of calculation should be individual medical services, and cost accounting should focus on specific units (centres of responsibility) of healthcare institutions.In addition, allocating indirect (overhead) costs is a significant problem, as these costs can account for a significant portion of total costs. The study analyzes various methods of allocating indirect costs, including direct, sequential and simultaneous allocation. It emphasizes the importance of selecting appropriate cost factors to ensure accurate pricing of healthcare services. Accurate cost allocation supports fair pricing and improves resource management and decision-making processes in healthcare organizations. Ultimately, the study emphasizes adapting traditional costing theories to the healthcare industry to increase healthcare delivery transparency, accountability, and efficiency.
Keywords: costing; cost price; expenses; accounting methods; methods of allocating indirect costs; responsibility centres; management; medical services